The potential benefits of targeted attentional bias modification on cognitive arousal and sleep quality in worry-related sleep disturbance - Milkins, B.; Notebaert, L.; MacLeod, C.; Clarke, Patrick (Sage Publications, 2016)
Attentional bias for sleep-related negative information is believed to contribute to symptoms of insomnia by elevating arousal during the presleep period. In the present study, we examined whether the delivery of an attentional bias modification (ABM) procedure in the presleep period could produce transient benefits for sleep-disturbed individuals by reducing presleep cognitive arousal and improving ease of sleep onset. In a counterbalanced repeated A-B design, participants alternated completing an ABM training task and a nontraining control task across six nights and reported on presleep cognitive arousal and sleep onset latency. Significant reductions in presleep cognitive arousal and sleep onset latency were observed on nights where the ABM task was completed relative to nights where the control task was completed. These results suggest that delivery of ABM can attenuate cognitive arousal and sleep onset latency and highlights the possibility that targeted delivery of ABM could deliver real-world benefits for sleep-disturbed individuals.